2022
DOI: 10.3201/eid2811.220615
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-Based Identification of Metronidazole-Resistant Clostridioides difficile Isolates

Abstract: C lostridioides difficile is a major cause of antibioticassociated colitis (1). Antimicrobial drug-resistant infections are a global economic and healthcare burden (2). Resistance is generally low to commonly prescribed antimicrobial drugs used for primary C. difficile infections. However, high rates of metronidazole resistance have been observed for C. difficile isolates carrying the 7-kb plasmid pCD-METRO, in particular for isolates belonging to PCR ribotype (RT) 010 and RT020 (clade 1) and the epidemic stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…The associated resistance mechanism is not yet understood. 22 Boekhoud et al 21 confirmed the presence of pCD-METRO in several metronidazole-resistant C. difficile strains that had been reported previously. 23–25 To date, plasmid-mediated metronidazole resistance has been found in C. difficile PCR ribotypes (RTs) RT010, RT020, RT005 and in one isolate of RT027.…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations
“…The associated resistance mechanism is not yet understood. 22 Boekhoud et al 21 confirmed the presence of pCD-METRO in several metronidazole-resistant C. difficile strains that had been reported previously. 23–25 To date, plasmid-mediated metronidazole resistance has been found in C. difficile PCR ribotypes (RTs) RT010, RT020, RT005 and in one isolate of RT027.…”
Section: Introductionsupporting
confidence: 58%
“… 23–25 To date, plasmid-mediated metronidazole resistance has been found in C. difficile PCR ribotypes (RTs) RT010, RT020, RT005 and in one isolate of RT027. 22 , 26 , 27 The majority of those isolates belonged to RT010 and were non-toxigenic. 22 Recently, a point mutation in the promoter of the nimB gene (dubbed ‘P nimB G ’) of C. difficile was reported to enhance the gene’s expression level and thereby elevate the metronidazole MIC by 4- to 8-fold.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Groups investigating drivers of antibiotic resistance should note that the combination of genomic and phenotypic resistance data provide the most robust information to evaluate functions of genomic loci in promoting resistance, and to exercise caution in interpreting resistance gene calls in the absence of phenotypic confirmation. For example, in C. difficile AMRFinderPlus has identified plasmid-borne genes that increase strain phenotypic resistance to metronidazole 68 . In contrast, many van gene homologs that are involved in C. difficile's cell wall synthesis, promote phenotypic resistance to vancomycin in Enterococci and other species, but do not do so in C. difficile 47 .…”
Section: Clostridial Genomic Analysis Of Virulence Factors and Antibi...mentioning
confidence: 99%